2011
DOI: 10.1063/1.3597831
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating negative capacitance in light-emitting diodes using an advanced semiconductor device theory

Abstract: The capacitance characteristics of light emitting diodes (LEDs) are accurately measured using a method based on an alternating-current small signal, together with direct current I-V plot. All measured LEDs display negative capacitance (NC) at large forward bias. By analyzing the dependence of capacitance on both forward bias and frequency, an accurate expression for describing NC was obtained. This expression is in conflict with Shockley's p-n junction theory, which only describes increasing diffusion capacita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
(22 reference statements)
2
16
0
Order By: Relevance
“…It was observed that the capacitance of the r-ELDs becomes negative for sufficiently high applied biases and low modulation frequencies. This negative capacitance (NC) behaviour has been reported previously for different type of devices like solar cells [2,3], p-i-n diodes [4], Schottky diodes [5,6] metal-insulator-semiconductor structures [7] including electroluminescent diodes [1,[8][9][10][11]. However, the explanations given by various groups for the occurrences of NC do not agree to a common argument.…”
Section: Introductionmentioning
confidence: 65%
“…It was observed that the capacitance of the r-ELDs becomes negative for sufficiently high applied biases and low modulation frequencies. This negative capacitance (NC) behaviour has been reported previously for different type of devices like solar cells [2,3], p-i-n diodes [4], Schottky diodes [5,6] metal-insulator-semiconductor structures [7] including electroluminescent diodes [1,[8][9][10][11]. However, the explanations given by various groups for the occurrences of NC do not agree to a common argument.…”
Section: Introductionmentioning
confidence: 65%
“…9 In the inset of Figure 2(a), we found that after a small increase, the apparent capacitance began to decrease and then became negative. In addition, corresponding to frequencies of l kHz, 10 kHz, and 100 kHz, the voltages where NC appears were different, as indicated by A, B, and C, respectively, in Figure 2(a).…”
mentioning
confidence: 94%
“…These results are similar to experimental results reported previously. 8,9 Therefore, we can use the same expression of NC:…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…We observed that as the forward bias increases, the reactive component of the impedance demonstrates negative capacitance (NC). Higher magnitude of this NC for lower applied modulation frequencies has also been observed by many groups in electroluminescent devices [5][6][7] and also in other semiconductor devices. 8,9 Here, we report qualitatively opposite dynamic behavior of NC in two sets of diodes with different functionalities: (a) III-V based electroluminescent diodes (ELDs): (i) InGaAs based quantum dot laser (QDL) diodes grown by Molecular Beam Epitaxy (MBE) on (100) GaAs substrates.…”
mentioning
confidence: 87%